Emergence of permanent teeth in Tanzanian children - Mugonzibwa EA, Kuijpers-Jagtman AM, Laine-Alava MT, van‘t Hof MA. (Blackwell Synergy, 2002)
The aim of the present study was to investigate the emergence of permanent teeth among Tanzanian children